Investigation on tee junction erosion caused by sand-carrying fracturing fluid - Yao, Liming (2023)
The high-speed flow of sand-carrying fracturing fluid through tee junctions causes severe erosion and affects the safety of the fracturing operation. This study improves the traditional computational fluid dynamics-discrete element method (CFD-DEM) to avoid the (dense particles) collision-leading abnormal penetration but also considers the influence of fracturing fluid viscosity on particle collisions. Then the tee junction erosion model under fracturing conditions is established and verified by experiments. The simulation analysis shows that with the increase of two-phase flow velocity and Stokes number, the dominant effect of particle motion and collision changes from viscous force to inertial force, and then the tee junction erosion position also changes.